Chimpanzees' (Pan troglodytes) strategic helping in a collaborative task - Melis, Alicia P.; Tomasello, Michael (Biology letters (2005), 2013)
Many animal species cooperate, but the underlying proximate mechanisms are often unclear. We presented chimpanzees with a mutualistic collaborative food-retrieval task requiring complementary roles, and tested subjects' ability to help their partner perform her role. For each role, subjects required a different tool, and the tools were not interchangeable. We gave one individual in each dyad both tools, and measured subjects' willingness to transfer a tool to their partner as well as which tool (correct versus incorrect) they transferred. Most subjects helped their partner and transferred the tool the partner needed. Thus, chimpanzees not only coordinate different roles, but they also know which particular action the partner needs to perform. These results add to previous findings suggesting that many of chimpanzees' limitations in collaboration are, perhaps, more motivational than cognitive.